The dynamics of the observed solar granulation: spatio-temporal variations of line of sight velocity and thermodynamic parameters - Baran, O.A. (Advances in Astronomy and Space Physics, 2014)
We investigated the dynamics of solar granulation, using the neutral iron line λ ≈ 639.3 nm profiles from highspatial resolution observations around the centre of the solar disc, in the non-perturbed region. We reproduced spatio-temporal variations of kinematic and thermodynamic parameters of solar convection at different heights of the solar photosphere (h = −25..550 km). The acoustic waves were removed by k − ω filtration. We analysed the temporal changes of these variations within convective cells.